(untitled) (Northern International Medical College Journal, 2020)
Background : Hematological malignancies (HM) was comprise approximately 6.5% of all cancer incidences worldwide in 2012. Although prevalence of these malignancies are much lower in Asia and Africa then in Western countries. The incidence of these malignancies is drastically increasing in low-income settings. WHO predicts that the number of bloodrelated cancer cases would be increased about 48% in less developed countries by 2030 as compared to 2012. Objective : In our study we tried to determine the current pattern of haematological malignancies among patients attending at the haematology department in a tertiary hospital. Methods : This cross-sectional observational study was carried out in outpatients and inpatients department of Haematology, Dhaka Medical College Hospital, Dhaka from 13th August 2016 to 12th august 2017 for a duration of 12 months. Detail clinical history, examination findings and investigations of patients were recorded in a pre-designed case record form. All data were converted to tabulated forms to obtain statistical information by Using Microsoft Excel and SPSS 17 program. Results : Out of 400 HM patients, most of them were male (66.75%) and remaining (33.25%) were female and male female ratio was 2.01:1. From rural were (71.25%) and remaining (28.75%) were urban population. Acute lymphoblastic leukaemia (ALL) patients were 87 (21.75%), mean age 25.4 years; Acute myeloid leukaemia (AML) patients were 81 (20.25%), mean age 36.5 years; Chronic myeloid leukaemia (CML) patients were 71 (17.75%), mean age 35.5 years; Non Hodgekin lymphoma (NHL) patients were 56 (14%), mean age 42.9 years; Acute promyelocytic leukaemia (APL) patients were 35 (8.75%), mean age 29.4 years; Multiple myeloma (MM) patients were 33 (8.25%), mean age 55.9 years; Hodgekin lymphoma (HL) patients were 24 (6.00%), mean age 33.8 years; Chronic lymphocytic leukaemia (CLL) patients were 7 (1.75%), mean age 61.9 years; Follicular lymphoma (FL) patients were 4 (1.00%), mean age 56.5 years; Mantle cell lymphoma (MCL) patient was 1 (0.25%), age 70 years and Burkitt lymphoma (BL) patient was 1 (0.25%), age 25 years. Conclusion : Study result showed that acute leukaemias were more common than chronic cases. AML and APL (subtype of AML) were more than ALL. Individually APL was the 5th in position whereas ALL was the 1st and AML was the 2nd highest cases among the 11 types of HM found in this study. Percentage of CML was higher (3rd in position) than CLL (8th in position) among the studied cases. Among the lymphomas NHL was more common (4th in position) than HL (7th in position) and MM (6th in position). FL (subtype of NHL) which is low grade in nature was 9th in position among the eleven. MCL and BL was rare and each was 1 in number in this study. Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 415-418